PERBANDINGAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SESUDAH STOCK SPLIT: Studi Pada Perusahaan Yang Terdaftar Di BEI Periode 2013-2022 - Adelita Vinya Tristanti (2023)
This quantitative study investigates the impact of stock split on abnormal return and trading volume activity by testing whether there are differences between pre- and post-stock split periods. A sample of 73 companies listed on the Indonesia Stock Exchange carrying out stock splits between 2013 and 2022 was used for analysis. The data was tested using the Wilcoxon signed rank test method via Eviews 12.0 software. Research findings shows that (1) There exists a difference in abnormal return before and after the stock split; (2) There is a difference in trading volume activity pre- and post-stock split.